ANATOMO - MORPHOLOGICAL FEATURES OF AN EDENTULOUS UPPER JAW - Yordanka Donkova; Anna Nenova-Nogalcheva; Desislava Konstantinova; Delyan Georgiev (Peytchinski Publishing, 2023)
Introduction: The success of prosthetic and implant treatment is determined by the knowledge of the anatomical and morphological features of upper and lower edentulous jaws and the identification of landmarks in the prosthetic field that contribute to accurate planning of the complete rehabilitation of the oral cavity. Purpose: This article aims to present and analyze anatomical and morphological features of an edentulous upper jaw that are important for the prosthetist. Materials and methods: A search was conducted in the period from October 2022 till December 2022 in the electronic databases PubMed, Google Scholar, ScienceDirect and several other bibliographic databases using the following keywords: anatomical features, upper jaw, atrophy, residual bone, complete prostheses, edentulous patients. Only literary sources in English, German, Bulgarian and Russian language were included. Rеsults: A total of 1076 articles were identified by the literature search, and the title and abstracts of the articles were examined. Twenty-eight original research studies met the inclusion criteria. Data and evidence were extracted for the importance of anatomical landmarks and features of the prosthetic field in case of complete tooth loss during prosthetic treatment. Conclusion: Individual anatomical and morphological features, age-related and functional changes that occur after complete tooth loss create conditions for prosthetics that must be tailored to the specifics of each individual clinical case and require an individual approach.